Konseling Gizi Media Booklet Terhadap Perilaku Pencegahan Anemia Pada Ibu Hamil - Mardiana Mardiana; Rina Mardiana; Yulianto Yulianto; Yuli Hartati (Poltekkes Kemenkes Semarang, 2022)
Background : Anemia in pregnant women has a bad impact on both mother and fetus, resulting in a long labor process and bleeding, premature fetuses, low weight birth babies, disability and even infant death. Based on the results of Riskesdas in 2018, there was a significant increase in the prevalence of anemia in pregnant women, namely 48.9%, still below the target of achieving indicators in the 2020-2025 Community Nutrition Directorate Activity Action plan to reduce the prevalence of maternal anemia in pregnant women to 42%.Purpose : to determine the influence of providing nutritional counseling on knowledge, attitudes, and efforts to prevent anemia in pregnant women.Methods: quasi experiment with pretest and post-test research designs. The study was conducted in March- April 2021. Data analysis using independent t test.Results: In the Independent t test conducted in both groups on knowledge and attitudes, a p-value value lt; 0.05 was obtained, while for actions, a p-value value of 0.05 was obtained.Conclusion: There are differences in increasing knowledge and attitudes, where the treatment group uses booklet media in an effort to prevent anemia in pregnant women compared to providing just nutritional counseling.